Food systems and building back better - Ebata, Ayako; Nisbett, Nicholas; Gillespie, Stuart (Institute of Development Studies, 2020)
Measures that have been put in place across the world to slow down the spread of coronavirus (Covid-19) have had profound effects on food and nutrition security for those furthest behind. In the short run, many have experienced increased commodity prices, decreased access to food through schools and markets, disrupted agri-food supply chains, and loss of livelihoods. It is feared that these short-term effects will have a long-term impact on poverty, intergenerational malnutrition among vulnerable people (in particular, pregnant and lactating women), agricultural productivity reduction, and increased conflicts and displacement. How can we build back food systems better after Covid-19 so that they serve the needs of those furthest behind? To guide this decision, we employ the following concept of food systems resilience: ‘Capacity over time of a food system and its units at multiple levels, to provide sufficient, appropriate and accessible food to all, in the face of various and even unforeseen disturbances’. In applying this concept to the post-Covid-19 response, we supplement this with a political economy angle that critically examines whose resilience is and should be prioritised in humanitarian aid and donor-funded interventions. In line with international and Ireland’s commitments, the aim is to build back food systems that ‘leave no one behind’.